A Structural Ricardian Analysis of Climate Change Impacts and Adaptations in African Agriculture - Seo, S. Niggol (World Bank, Washington, DC, 2012)
This paper develops a Structural Ricardian model to measure climate change impacts that explicitly models the choice of farm type in African agriculture. This two stage model first estimates the type of farm chosen and then the conditional incomes of each farm type after removing selection biases. The results indicate that increases in temperature encourage farmers to adopt mixed farming and avoid specialized farms such as crop-only or livestock-only farms. Increases in precipitation encourage farmers to shift from irrigated to rainfed crops. As temperatures increase, farm incomes from crop-only farms or livestock-only farms fall whereas incomes from mixed farms increase. With precipitation increases, farm incomes from irrigated farms fall whereas incomes from rainfed farms increase. Naturally, the Structural Ricardian model predicts much smaller impacts than a model that holds farm type fixed. With a hot dry climate scenario, the Structural Ricardian model predicts that farm income will fall 50 percent but the fixed farm type model predicts farm incomes will fall 75 percent.